Determinants of economic growth in Nigeria - Kazeem B. Ajide (CBN Journal of Applied Statistics, 2014)
This paper investigates the role of Frazer Economic Freedom Index on FDI-growth relationship over the period spanning 1980 through 2010 using annual time series data. A Multivariate Regression approach was employed to estimate augmented growth models. Quite intriguingly, the impact of disaggregated economic freedom over aggregated composite index was found profoundly revealing. Emanated results show that the same set of variables like labour, life expectancy, degree of openness and economic freedom are factors affecting the level of economic growth in both but at different levels of significance. However, the estimates of disaggregated components of economic freedom data show that the size of government (negative effects) and freedom to trade internationally (positive effects) appears as significant out of five variables making the composite (aggregated) index. The following are therefore suggested for policy applications: curbing unfettered liberalization in the degree of openness, improving and strengthening of the components of economic freedom index, specifically, through reduction in excessive government intervention and that more budgetary allocations should be channeled towards health delivery schemes and education promoting activities since the likelihood of elongating life expectancy is in tandem with such exercises.
Keywords: CO1; E22; O43; 330; Economic Freedom; FDI; Economic Growth; Multivariate Regression Approach